Konstruksi Realitas Sosial dalam Akun Instagram @J.S. Khairen (Analisis Semiotika Roland Barthes) - Reva Widyanti; Silvina Mayasari; Sari Ekowati Hadi (CV Edujavare Publishing, 2025)
The construction of political awareness through social media is no longer a challenging endeavor. Every segment of society now possesses the ability to voice justice with ease. However, the manifestation of freedom of expression and democratic participation in public spaces is increasingly perceived as a threat by the government—often justified by political, security, or moral interests used as a pretext to restrict civic expression. One such form of restriction is the silencing of public voices. This study examines how the social reality surrounding the silencing of public expression is represented through the Instagram account @j.s.khairen. The primary objective of this research is to raise public awareness regarding the phenomenon of government suppression of citizens' aspirations, as portrayed through subtle symbolic representations on social media platforms. Employing a qualitative approach within the constructivist paradigm, this study utilizes Roland Barthes’ semiotic analysis method to interpret the denotative, connotative, and mythological meanings embedded in the visual and textual content posted on the account. The findings indicate that the @j.s.khairen account consistently articulates socio-political critique through compelling visual symbols and narratives, serving as a form of resistance against the suppression of public discourse. In conclusion, social media functions as an alternative platform for voicing truth and fostering political consciousness in the midst of increasingly constrained democratic spaces.